2019
DOI: 10.1113/jp277884
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model of gestational glucose intolerance through exposure to a low protein diet during fetal and neonatal development

Abstract: Key points Pancreatic β‐cell dysfunction is hypothesized to be the significant determinant of gestational diabetes pathogenesis, however pancreatic samples from patients are scarce. This study reports a novel mouse model of gestational glucose intolerance in pregnancy, originating from previous nutrition restriction in utero, in which glucose intolerance was restricted to late gestation as is seen in human gestational diabetes. Glucose intolerance was attributed to reduced β‐cell proliferation, leading to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(55 citation statements)
references
References 62 publications
(123 reference statements)
1
54
0
Order By: Relevance
“…These data could implicate a contribution for α-cell neogenesis from small endocrine clusters to the adaptive expansion of ACM at GD18.5, which has also been shown to be a mechanism of BCM expansion. 7,8,25 However, our data suggest that adaptive α-cell mechanisms were impaired in GDM.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…These data could implicate a contribution for α-cell neogenesis from small endocrine clusters to the adaptive expansion of ACM at GD18.5, which has also been shown to be a mechanism of BCM expansion. 7,8,25 However, our data suggest that adaptive α-cell mechanisms were impaired in GDM.…”
Section: Discussionmentioning
confidence: 53%
“…7,8 GD18.5 was chosen as this is the timepoint where BCM is maximal in a control pregnancy 7,8 but has been shown to be reduced in GDM pregnancy resulting in glucose intolerance. 8 Females (F1) were euthanized by CO 2 asphyxia for comparison to non-pregnant age-matched F1 females. The pancreas was removed at each assigned day of gestation ( n = 4–6 C and LP animals for each timepoint during gestation and for the non-pregnant groups), fixed in 4% paraformaldehyde for histology and embedded in optical cutting temperature compound.…”
Section: Methodsmentioning
confidence: 99%
“…In another mouse model, researchers used the F1 offspring born to dams fed a low-protein (LP) diet during gestation and lactation. The F1 females develop glucose intolerance and reduced β-cell proliferation during pregnancy [ 196 ]. These models demonstrated that exposure to GDM or glucose intolerance during gestation increases the susceptibility of the offspring (F1) to developing GDM.…”
Section: Preclinical Models Of Gdmmentioning
confidence: 99%
“…In a recent issue of The Journal of Physiology , Szlapinski and colleagues demonstrated that pregnant mice classified as having GDM displayed pancreata with significantly decreased α‐ and β‐cell mass, corresponding to an overall decrease in insulin production and secretion, and therefore a globally reduced glucose sensitivity (Szlapinski et al . ). This pathology represents approximately 80% of GDM cases, which are classified based on β‐cell dysfunction with previous history or worsening peripheral insulin resistance (Plows et al .…”
mentioning
confidence: 97%
“…Maternal placental hormones then trigger a response in pancreatic β-cells to attempt to restore euglycaemia -β-cells and often α-cells of the pancreas undergo hypertrophy and hyperplasia. In a recent issue of The Journal of Physiology, Szlapinski and colleagues demonstrated that pregnant mice classified as having GDM displayed pancreata with significantly decreased αand β-cell mass, corresponding to an overall decrease in insulin production and secretion, and therefore a globally reduced glucose sensitivity (Szlapinski et al 2019). This pathology represents approximately 80% of GDM cases, which are classified based on β-cell dysfunction with previous history or worsening peripheral insulin resistance (Plows et al 2018), indicating a diabetic disorder that includes aspects of all three major categories of the disease (Type I, Type II and other).…”
mentioning
confidence: 99%